The expert consultation on the development of a comprehensive global record of fishing vessels : (Food and Agriculture Organization of the United Nations, 2008)
The goals of the Expert Consultation were to advise FAO on the development and implementation of a global record of fishing vessels and to respond to the request from FAO's Committee on Fisheries to further develop the concept as described in the feasibility study. A comprehensive global record, a potential additional tool to combat illegal, unreported and unregulated fishing, is envisioned as a global database gathering data from many sources in one location.